I tried it this way:

$$ 40\cosθ+9\sinθ=41 $$

$$ 9\sinθ=41-40\cos\theta $$

Squaring both the sides:

$$81\sin^2\theta=1681+1600\cos^2\theta-2\cdot 40\cdot 41 \cos\theta$$

$$81-81 \cos^2\theta= 1681+1600\cos^2\theta-3280 \cos\theta$$


Solving the quadratic equation gives $\cos\theta=\dfrac{40}{41}$. It is not easy to solve the quadratic equation without calculator so there must be some other method, if yes then please explain.

P.S: I've found the other method so I am self-answering the question.

  • $\begingroup$ So, You first typed answer then question? $\endgroup$ – user190024 Nov 6 '14 at 4:36
  • $\begingroup$ @Infinity Actually simultaneously on satckedit.io $\endgroup$ – user103816 Nov 6 '14 at 4:37
  • 1
    $\begingroup$ @user31782 There is an error in you quadratic. It should read $$1681\cos^2\theta-3280\cos\theta+1600=0$$. $\endgroup$ – John Joy Nov 7 '14 at 18:36

Using Brahmagupta-Fibonacci Identity,

$$(9\sin\theta+40\cos\theta)^2+(40\sin\theta-9\cos\theta)^2=(40^2+9^2)(\sin^2\theta+\cos^2\theta)=41^2$$ as $41^2=40^2+9^2$

So, $40\sin\theta-9\cos\theta=0$ and $9\sin\theta+40\cos\theta=41$

Can you solve for $\cos\theta$

  • $\begingroup$ Thankyou for the answer, it is quite interesting and of course short. $\cos\theta$ can be easily computed from $\tan\theta$. $\endgroup$ – user103816 Nov 6 '14 at 4:40
  • $\begingroup$ $\tan\theta=9/40$ and then using $1+\tan^2\theta=sec^2\theta$. $\endgroup$ – user103816 Nov 6 '14 at 4:42
  • 1
    $\begingroup$ @user31782, Squaring should generally be avoided as it immediately introduces extraneous root $\endgroup$ – lab bhattacharjee Nov 6 '14 at 4:44
  • $\begingroup$ Do you mean that I should solve $40\sin θ−9\cos θ=0$ by using $9=r\sin y,40=r\cos y$? But we can use this substitution directly in $9\sin θ+40\cos θ$ as you did in the other answer. So what is the benefit of using the Brahmagupta-Fibonacci Idintity. $\endgroup$ – user103816 Nov 6 '14 at 9:17
  • 1
    $\begingroup$ @user31782, Here we don't need to use $9=r\sin y$ etc. We just need to solve the two linear simultaneous equations for $\cos\theta$ $\endgroup$ – lab bhattacharjee Nov 6 '14 at 9:20

Squaring should generally be avoided as it immediately introduces extraneous root

Write $9=r\sin y,40=r\cos y$ where $r>0$

Squaring & adding we get, $r^2=41^2\implies r=41$

So, we have $r\cos(\theta-y)=41\iff\cos(\theta-y)=1=\cos0\implies\theta-y=2m\pi$ where $m$ is any integer

So, $\cos\theta=\cos(y+2m\pi)=\cos y=\dfrac{40}r $


Look at the work that you have already done. You know that $1681=41^2$, that $3280=2\cdot 40\cdot 41$, and that $1600=40^2$. You found this out when you squared $41-40\cos\theta$. It should now be quite easy to solve the quadratic $$1681\cos^2\theta−3280\cos\theta+1600=0$$ $$41^2\cos^2\theta−2(41)(40)\cos\theta−40^2=0$$ $$(41\cos\theta-40)^2=0$$ $$\dots$$

If you prefer to use the quadratic formula, remember to factor before you evaluate the square root.

$$\begin{array}{lll} \cos\theta &=& \frac{3280\pm\sqrt{3280^2-4(1681)(1600)}}{2\cdot 1681}\\ &=&\frac{2\cdot40\cdot41\pm\sqrt{(2\cdot40\cdot41)^2-4(41^2)(40^2)}}{2\cdot 41\cdot41}\\ &=&\frac{2\cdot40\cdot41}{2\cdot 41\cdot41}\\ &=&\frac{40}{41}\\ \end{array}$$

  • $\begingroup$ I have done that. Actually when I solved the discriminant with calculator, I saw it becoming 0. I was solving 1681 sin^2 - 738 sin + 81 = 0 and then 9 sin = 41 - 40 cos. I squared the later one: $ 9^2 - 9^2\cos^2 x =41^2 +40^2 \cos^2 x - 2\cdot 41\cdot 40$ then $ ( 40^2 + 9^2) \cos^2 x- 2\cdot40\cdot41 + (41^2-9^2)$ Then I eventually noted $ ( 40^2 + 9^2)= 41^2$. Thankyou for your answer. $\endgroup$ – user103816 Nov 8 '14 at 7:33

I noted that $9,40$ and $41$ are pythagorean triple, i.e $9^2+40^2=41^2$. This fact can be used to solve the question easily. I'll show the solution for the general case:
$a\cos\theta+b\sin\theta=c,$ given that $a^2+b^2=c^2$

$$a\cos\theta+b\sin\theta=c$$ $$b\sin\theta=c-a\cos\theta$$ Squaring both the sides: $$b^2\sin^2\theta=c^2+a^2\cos^2\theta-2ca\cos\theta$$ Substituting $c^2$ with $a^2+b^2$ gives: $$b^2\sin^2\theta=a^2+b^2+a^2\cos^2\theta-2ca\cos\theta$$ $$a^2+b^2\cos^2\theta+a^2\cos^2\theta-2ca\cos\theta=0$$ $$a^2+(a^2+b^2)\cos^2\theta-2ca\cos\theta=0$$ $$a^2+(c\cos\theta)^2-2a(c\cos\theta)=0$$ $$(a-c\cos\theta)^2=0$$ $$\cos\theta=\dfrac{a}{c}$$

Substituting $c=41$ and $a=40$ will give the solution of the particular equation discussed in the question.

An interesting thing is that $\sin\theta=\sqrt{1-\dfrac{a^2}{c^2}}=\dfrac{b}{c}, $ , i.e the equation actually belongs to a right angled triangle having $a$ as its base, $b$ as its prependicular and $c$ as its hypotenuse.

There is another method in which we divide both sides of the equation with $\sqrt{a^2+b^2}$ and then use the identity: $\sin (A+B)=\sin A \cos B+\cos A \cos B$

This method will give the same results.


Consider a right angled triangle having base $a$, perpendicular $b$ and hypotenuse $c$. We have:

$$\cos\theta=\dfrac{a}{c}\ \ \text{and}\ \ \ \sin\theta=\dfrac{b}{c}$$ $$\implies a=c\cos\theta \ \ \ \text{and}\ \ \ b=c\sin\theta$$

By the pythagoras theorem: $$a^2+b^2=c^2 $$ $$\implies\ c^2\cos^2\theta+c^2\sin^2\theta=c^2$$ $$\implies c\cos\theta \cdot c\cos\theta + c\sin\theta \cdot c\sin\theta=c^2$$ $$\implies a\cos\theta+b\sin\theta=c$$


Since $41^2 - 40^2 = (41-40)(41+40) = 81 = 9^2$, there exists an angle $\phi$ satisfying $$\sin \phi = \frac{40}{41}, \quad \cos \phi = \frac{9}{41},$$ hence $$\begin{align*} 1 &= \frac{9}{41} \sin \theta + \frac{40}{41} \cos \theta \\ &= \sin\theta \cos\phi + \cos\theta \sin\phi \\ &= \sin(\phi+\theta),\end{align*}$$ from which it follows that $\phi+\theta = \pi/2 + 2\pi k$ for some integer $k$, hence $$\cos\theta = \cos\left(\frac{\pi}{2} + 2\pi k - \phi\right) = \cos\left(\frac{\pi}{2} - \phi\right) = \sin\phi = \frac{40}{41},$$ and we are done.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.